INFORMATIONAL AND STRUCTURAL MODEL OF BIOECOMEDICINE - Khrystova, Tetiana; Kovalchuk, Oksana (International Multidisciplinary Scientific GeoConference SGEM, 2021)
One of the most important modern problems of society in terms of transformation is human 's health. A new interdisciplinary scientific direction-bioecomedicine is substantiated The theoretical and methodological basis of the work was the integrated use of scientific principles and a systematic approach, which led to the choice of research methods: general scientific, interdisciplinary. The contemporary definition was formulated and construction of information-structural model of bioecomedicine was characterized. The object, subject, basic method and basic concepts of this branch of science were defined; list of tasks on this issue is opened. The principles of unity of information space of bioecomedicine are characterized: generalization of information field of knowledge; systemcity of research; homeostasis at different levels of organization of biosystems; adequacy of system-environmental interaction; evolutionary compensation; humanization; ethics and aesthetics of human interaction with ecoenvironments; intellectualization of the information space of this branch of science. It is established that purposeful synthesis of information data from biology, ecology and medicine is possible on the basis of creation of unified informational space of bioecomedicine with the usage of the newest information technologies.